Elementary teacher’s perspective critical thinking process in analyzing mathematics problems: Right triangles - Erna Yayuk; Dyah Worowirastri Ekowati; Arina Restian (Universitas Muhammadiyah Malang, 2024)
In the learning process that occurs, many students work quickly, but the results obtained are not accurate. This is because students do not carry out the evaluation process. This research aims to analyze students’ critical thinking processes in solving mathematics problems. The questions discussed are flat geometry material, especially right triangles. The research method used is descriptive qualitative. The subjects were 13 students Elementary School Teacher, Faculty Teacher Training and Education, University Muhammadiyah of Malang. Subjects were selected using the purposive sampling method. The questions were given to 50 potential respondents and only 13 students were able to analyze them correctly. This research has resulted in 13 subjects being able to write information using their language at the interpretation stage. In the analysis stage, this subject can find the latest information by connecting previous knowledge with information obtained while studying in class. Evaluation Stage, 13 subjects were able to carry out the evaluation process by linking the main information found. In the interpretation stage, all subjects can draw a conclusion accompanied by reasons to support the answers and conclusions obtained. Communication and regulation stage, 13 subjects were able to communicate and carry out the process well.